THE CORELATION OF PARENTS USING THERAPEUTIC COMMUNICATION WITH THE LENGTH OF TIME USING GADGETS IN A DAY 24 HOURS IN EARLY CHILHOOD (3-8 YEARS OLD) IN CIANTRA VILLAGE PEACOCK ALLEY IX 2022 - Utami, Sri (Rena Cipta Mandiri, 2022)
The flow of globalization that cannot be separated from human life at this time which greatly affects daily life, one of which is communication. Communication is the provision of infomation, news, or interaction carried out by two or more people in the hope that there will be feedback given after listening to the information. The communication tool that can be used in this case is using therapeutic communication. Therapeutic communication can not only be done by nurses but parents to see the lenght of time using gadgets that occur in children. Gadgets is a telecomunications medium taht has ad small form that is easy to carry and is widely used today. This is clear evidence of the development of science and tacholog (science technology) at this time, gadgets are able to influence humans both in terms of mindset and behavior. The study aims to determine”The Corelation Of Parents Using Therapeutic Communication With The Length Of Time Using Gadgets In A Day 24 Hours In Early Chilhood (3-8 Years Old) In Ciantra Village Peacock Alley IX 2022”. The type of quantitative research with cross sectional method. The population is parents who have an early age of 3-8 years with a total of 34 respondents. Sampling techique using total sampling. The result obtained with a significannt level of 95% of a value of 5% (0,05) obtained p value (0,000) < value (0,05) so taht it can be concluded from these results that H0 is rejected, meaning that there is a The Corelation Of Parents Using Therapeutic Communication With The Length Of Time Using Gadgets In A Day 24 Hours In Early Chilhood (3-8 Years Old) In Ciantra Village Peacock Alley IX 2022. There is a The Corelation Of Parents Using Therapeutic Communication With The Length Of Time Using Gadgets In A Day 24 Hours In Early Chilhood (3-8 Years Old) In Ciantra Village Peacock Alley IX 2022. Arus globalisasi yang tidak bisa terlepaskan pada kehidupan manusia pada saat ini yang mana sangat mempengaruhi kehidupan sehari-hari salah satunya komunikasi. Komunikasi merupakan pemberian informasi, berita, atau interaksi yang dilakukan oleh dua orang atau lebih dengan harapan ada feedback yang diberikan setelah mendengarkan informasi tersebut. Alat komunikasi yang bisa digunakan dalam hal ini yaitu menggunakan komunikasi terapeutik. Komunikasi terapeutik tidak hanya bisa dilakukan oleh perawat tetapi orang tua untuk melihat lama waktu penggunaan gadget yang terjadi pada anak. Gadget suatu media telekomunikasi yang memiliki bentuk yang kecil yang mudah dibawa dan banyak digunakan pada saat ini. Ini merupakan bukti nyata perkembangan iptek ( ilmu pengetahuan teknologi ) pada saat ini, Gadget mampu mempengaruhi manusia baik dari segi pola pikir ataupun perilaku. Penelitian ini bertujuan untuk mengetahui “Hubungan Orang Tua Menggunakan Komunikasi Terapeutik Dengan Lama Waktu Penggunaan Gagdet Dalam Sehari 24 Jam Pada Anak Usia Dini (3-8 tahun) Di Desa Ciantra Gang Merak IX Tahun 2022”. Jenis penelitian kuantitatif dengan metode cross sectional. Populasi adalah orang tua yang memiliki anak usia dini 3-8 tahun dengan jumlah 34 responden. Teknik pengambilan sample dengan menggunakan Total Sampling. Didapatkan hasil dengan tingkat signifikan 95% atau nilai a 5% (0,05) diperoleh p value (0,002) < nilai a (0,05) sehingga dapat disimpulkan dari hasil tersebut H0 ditolak artinya ada Hubungan Orang Tua Menggunakan Komunikasi Terapeutik Dengan Lama Waktu Penggunaan Gadget Dalam Sehari 24 Jam Pada Anak Usia Dini (3-8 Tahun) Di Desa Ciantra Gang Merak IX Tahun 2022. Ada Hubungan Orang Tua Menggunakan Komunikasi Terapeutik Dengan Lama Waktu Penggunaan Gagdet Dalam Sehari 24 Jam Pada Anak Usia Dini (3-8 tahun) Di Desa Ciantra Gang Merak IX Tahun 2022.